KOMPOSISI JENIS DAN STRUKTUR HUTAN MANGROVE DI AREAL BEKAS TEBANGAN IUPHHK PT. BINA OVIVIPARI SEMESTA KABUPATEN KUBU RAYA - Selfiany, Widiya Octa; Muin, Abdurrani; Burhanuddin, . (Universitas Tanjungpura, 2018)
This study aims to study and get a picture of species composition and structure of mangrove forests in logged-over areas of 2012, 2014 and 2016 at PT. Bina Ovivipari Semesta Kubu Raya District West Kalimantan Province. The method used in this study was the survey method by way of plotted path, where the laying of the path done by purposive sampling. The results of seedling to tree level showed that of 5 mangrove species found; Mangrove (Rhizophora apiculata), Tumu (Bruguiera gymnorrhiza), Lenggadai (Bruguiera parviflora), Nyirih Batu (Xylocarpus mullocensis) and Blukap (Rhizophora mucronata), the highest diversity index was owned by Rhizophora apiculata Blume species with values from 0.03-0.77; while the lowest diversity index was owned by Rhizophora mucronata species with a value of 0.01. From Index range values ranging from seedling to tree level indicates that the diversity index of logged-over areas of 2012, 2014 and 2106 of mangroves were in the low range.Keywords: mangrove forest, species composition, structure of mangrove.